Effects of attentional loadings on turning kinematics in stroke survivors / Mohd Haidzir Abd Manaf - Abd Manaf, Mohd Haidzir (Institute of Graduate Studies, UiTM, 2015)
The purpose of this study was (1) to compare temporal-spatial gait parameters and axial segmental coordination across attentional loading conditions during Timed Up and Go test (TUG), and (2) to determine the correlation between gait parameters across attentional loading conditions during TUG and, level of sensorimotor impairment, and functional balance in stroke survivors. Thirty stroke survivors participated in this study. Temporal-spatial gait parameters (gait speed, stride time, stride length, turn time and number of steps) and axial segmental coordination across single, dual-motor and dual-cognitive task were measured during the Timed Up and Go (TUG) test. Researcher further divided the TUG test into turning and straight walking phases to gain information about whether attentional loading had a differential effect on each phase. A repeated measure ANOVA and the Spearmen’s rank correlation coefficient were used to analyse the data. The temporal-spatial gait parameters taken during TUG test was increased significantly from single- to dual-task conditions (dualmotor and dual- cognitive)…